How Westin Hotels and Four Seasons leveraged symbolic values to build their brands - Brookes, Maureen (Henry Stewart Talks, 2017)
This case study describes how Starwood developed the Westin chain of hotels as an upmarket, health-conscious brand by emphasizing service as well as symbolic and emotional values, and compares this to the way the Four Seasons hotel chain developed its image as a luxury brand.